Enhanced Perioperative Care for Major Spine Surgery. Issue 13 (1st July 2019) - Dagal, Armagan; Bellabarba, Carlo; Bransford, Richard; Zhang, Fangyi; Chesnut, Randall M.; O'Keefe, Grant E.; Wright, David R.; Dellit, Timothy H.; Painter, Ian; Souter, Michael J.
Abstract : Study Design: The enhanced perioperative care (EPOC) program is an institutional quality improvement initiative. We used a historically controlled study design to evaluate patients who underwent major spine surgery before and after the implementation of the EPOC program. Objective: To determine whether multidisciplinary EPOC program was associated with an improvement in clinical and financial outcomes for elective adult major spine surgery patients. Summary of Background Data: The enhanced recovery after surgery (ERAS) programs successfully implemented in hip and knee replacement surgeries, and improved clinical outcomes and patient satisfaction. Methods: We compared 183 subjects in traditional care (TRDC) group to 267 intervention period (EPOC) in a single academic quaternary spine surgery referral center. One hundred eight subjects in no pathway (NOPW) care group was also examined to exclude if the observed changes between the EPOC and TRDC groups might be due to concurrent changes in practice or population over the same time period. Our primary outcome variables were hospital and intensive care unit lengths of stay and the secondary outcomes were postoperative complications, 30-day hospital readmission and cost. Results: In this highly complex patient population, we observed a reduction in mean hospital length of stay (HLOS) between TRDC versus EPOC groups (8.2 vs. 6.1 d, standard deviation [SD] = 6.3 vs. 3.6, P < 0.001) and intensive care unit length of stay (ILOS) (3.1 vs. 1.9 d, SD = 4.7 vs. 1.4, P = 0.01). The number (rate) of postoperative intensive care unit (ICU) admissions was higher for the TRDC n = 109 (60%) than the EPOC n = 129 (48%) ( P = 0.02). There was no difference in postoperative complications and 30-day hospital readmissions. The EPOC spine program was associated with significant average cost reduction—62, 429 to 53, 355 ( P < 0.00). Conclusion: The EPOC program has made a clinically relevant contribution to institutional efforts to improve patient outcomes and value. We observed a reduction in HLOS, ILOS, costs, and variability. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textWe investigated whether adult patients planned to undergo elective major spine surgery benefit from comprehensive multidisciplinary perioperative medicine program? The EPOC program was associated with a reduction in length of stays, postoperative ICU admissions, and cost, while there was no difference in complication and hospital readmission rates.